PENGARUH GAYA KOLONIAL BELANDA PADA INTERIOR RUMAH TINGGAL DI KAYUTANGAN MALANG - Grace Setiati (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Kristen Duta Wacana Yogyakarta, 2017)
Title : The Influence of Dutch Colonial Style on Design Residential in Kayutangan Malang Malang is referred to as one of the best products of colonial town planning in the Dutch East Indies. The city center of Malang in 1914 is located in the Kayutangan to Malang town square. Region Kayutangan a commercial area of Malang in the Dutch colonial occupation. Influence of development of Dutch colonial architecture included in the settlement of indigenous people, so with Kayutangan. This study aims to assess the legacy of Dutch colonial style design of houses in the area Kayutangan Malang. The research method using descriptive qualitative method with case studies. Research result shows there are significant design style colonial with the adaptation of local materials and adapted to the tropical climate in the city of Malang, there is also a mixing effects of European culture, Chinese traditional culture and the Java community. Colonial design style is manifested in the physical building with simplification of forms, according to ability, interpretation and technologies currently owned and maintained until now.